The Effect Of Tax Sanctions, Tax Knowledge, and Tax Services on Taxpayer Compliance in E-Commerce Businesses with Taxpayer Awareness as a Moderating Variable - Mei Welensya Br Simatupang; Kiko Armenita Julito; Robiur Rahmat Putra (Return : Study of Management, Economic and Bussines, 2023)
This study aims to examine the effect of tax sanctions (SP), tax knowledge, tax services and taxpayer awareness on taxpayer compliance in e-commerce businesses. The sampling technique used in this study was purposive sampling. The sample in this study was 321 from the E-commerce business community in the Jakarta area. This type of research is quantitative research with data collection techniques, namely the method of distributing questionnaires via Google form using a Likert scale. The data processing method in this study uses Smart PLS software which is used to test hypotheses. The results of this study indicate that tax sanctions have proven to have a positive and significant effect on e-commerce business taxpayer compliance commerce. The results of this study recommend that creating E-commerce Business Taxpayer Compliance in individuals is to have good Tax Knowledge on Taxpayers (WP).